(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The paper discusses prerequisites of recreational potential of the Lori Province, presents ways of using them effectively. Lori is a province with unique natural history, touristic-recreational attractiveness and significant potential for development, and can offer a diverse, competitive recreational and touristic products and services. The province stands out with numerous natural and manmade recreational resources, which have contributed to the development of recreational and health tourism. Factors such as the diverse landscape, lush forests, favorable and healthful climate, lakes, crystal clear mountain rivers, mineral sources with diverse mineralization and temperatures, many natural, historical and cultural monuments have important practical role for the sector. However, the recreational and touristic potential of the province is underutilized; the level of utilization of the potential is very low. The recreational resources of the province are currently underrepresented in the tourism market. In order to improve the attractiveness, the attractive recreational locations of the province must be mapped, and the services offered should be advertisement more actively. More cooperation with the tour operators is required to include Lori Province in larger number of tours, improving the visibility and recognizability of the province, which will solidify the province’s role position in the recreational market.